Synthesis of precision dosing systems for liquid products based on electropneumatic complexes - Gavva, Oleksandr M.; Kryvoplias-Volodina, Liudmyla; Blazhenko, Serhii; Tokarchuk, Serhii; Derenivska, Anastasiia (My University, 2021)
This paper reports the construction of a mathe-matical model for the process of dosing liquid foods (non-carbonated drinking water). The model takes into consideration the differential equations of chang-es in the kinematic parameters of the liquid in a dos-ing device's channels and the corresponding accept-ed initial and boundary conditions of the process. The boundary conditions account for the influence of soft-ware-defined airlift dosing modes using the driver and the geometry of the product pipeline. The current's value measured in mA (with an accuracy of 0.001 mA) relative to the standard scale Imin is Imax=4...20 mA.Individual stages of the dosing process were ana-lytically described, followed by the analysis of sepa-rate stages and accepted assumptions.The accuracy achieved when testing the experi-mental sample of the dispenser, with the repetition of the dose displacement process, ranged between 0.35 % and 0.8 %. The reported results are related to the established dosage weight of 50 ml when changing the initial level of liquid in the tank of the dosing feeder by 10 mm.An experimental bench has been proposed for investigating the functional mechatronic dosing mod-ule under the software-defined modes to form and discharge a dose of the product. The bench operates based on proportional feedback elements (4–20 mA) for step and sinusoidal pressure control laws in the dosing device.The control model with working dosing modes has been substantiated. The control models built are based on proportional elements and feedback.During the physical and mathematical modeling, the influence of individual parameters on the accuracy of the product dose formation was determined; ways to ensure the necessary distribution of compressed air pressure, subject to the specified productivity of the dosing feeder, were defined. The study results make it possible to improve the operation of precision dosing systems for liquid products based on electro-pneumat-ic complexes.
Keywords: dose discharge; feedback; dosing accuracy; airlift system; excess pressure; розряд дози; ерліфтна система; надлишковий тиск; зворотний зв'язок; точність дозування; кафедра мехатроніки та пакувальної техніки; кафедра технологічного обладнання та комп’ютерних технологій проектування